A Common-Sense Model Perspective on Illness Perception, Adherence Behaviors, and Quality of Life in Hemodialysis Patients - Natashia, Dhea; Fitria, Dian; Rismawati, Rini; Aisya Adif, Shannastaniar (UNIVERSITAS MUHAMMADIYAH SURABAYA, 2025)
Background: Patients with chronic kidney disease undergoing hemodialysis face substantial symptom burdens that may influence adherence behaviors and overall quality of life. The Common-Sense Model (CSM) proposes that illness perception shapes coping responses, including adherence, which subsequently affect health outcomes. However, the relationships among these variables remain inconsistent, particularly in the Indonesian context. Objective to examine the associations among illness perception, adherence behaviors, and quality of life in patients with chronic kidney disease undergoing hemodialysis from a Common-Sense Model perspective.Methods A cross-sectional study was conducted among adult patients with chronic kidney disease undergoing hemodialysis in two dialysis centers. Illness perception was assessed using the Brief Illness Perception Questionnaire; adherence behaviors using the End-Stage Renal Disease Adherence Questionnaire (ESRD-AQ); and quality of life using the KDQOL-SF. Pearson correlation tests were used to analyze associations among variables. Results Illness perception was not significantly associated with adherence behaviors or any quality-of-life domain. In contrast, specific adherence behaviors demonstrated significant relationships with mental health outcomes. Adherence to fluid restrictions was positively associated with the Mental Component Summary (MCS) (r = 0.302, p < 0.01), and dietary adherence also correlated with MCS (r = 0.238, p < 0.05). No adherence variable was associated with the Physical Component Summary (PCS). Interdialytic Weight Gain (IDWG) showed negative correlations with PCS (r = –0.250, p < 0.05) and the burden-of-kidney-disease domain (r = –0.278, p < 0.05), indicating poorer physical well-being with higher fluid accumulation. Conclusion: Within the CSM framework, illness perception did not predict adherence or quality of life. Adherence to dietary restrictions, adherence to fluid restrictions, and effective fluid management emerged as important correlates of both the mental and physical aspects of quality of life. Interventions that strengthen behavioral adherence and promote optimal fluid control may provide greater improvements in patient well-being compared to approaches that focus only on modifying illness perceptions